(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Wind energy is obtained converted into usable mechanical energy by means of a wind turbine.It is also possible to use mechanical power directly for certain purposes, such as water pumping. Windis produced on by the sun’s uneven heating of the atmosphere, surface fluctuations Earth’s rotation.This means that wind power generation is best suited to specific geographic areas. Offshore wind farmscan be built in huge lakes oceans as well as on land. Horizontal-axis wind turbines (similar to windmills) are more prevalent than their vertical-axis counterparts. This study examines Vestas’ logistics forgetting wind turbines from their factory in Aarhus, Denmark, to customers in the United States. Logisticsis the management of the flow of goods between a company and its suppliers between the companyand its customers.